Government Expenditure And Private Investment In Ghana - Awuni, P.D. (University Of Ghana, 2021)
The drive to encourage private sector participation in the Ghanaian economy has led to the implementation of some pro-private sector development policies that involved government spending in expanding energy, health, education and road infrastructure. The economic literature however remains inconclusive about the effectiveness of this increase in government expenditure on private investments and whether any potential threshold effects exist. Accordingly, this thesis tests the hypothesis for the case of Ghana by exploring the threshold effect of government expenditure on private investment in Ghana using annual time series data from 1984 to 2018. The study employed the Threshold Autoregressive (TAR) model to ascertain the optimal level of government expenditure that promotes private investment by addressing asymmetric and non-linear deficiencies of the usual linear models applied in previous studies. The main finding of the study revealed that the threshold value of government expenditure is 13.38% of GDP. Below the threshold value, government spending crowds-out private investment while government expenditure above the threshold crowds-in private investment. Hence, the relationship between government expenditure and private investment is non-linear; specifically, it is U-shaped. The causality test conducted reveals a unidirectional causality from government expenditure to private investment. The study recommends more government spending towards increasing social capital while taking steps to minimize spending inefficiencies emanating from abandoning state projects, rent-seeking and, the maximization of personal and political interest. Finally, the study recommends targeted tax incentive policy to productive sectors of the economy.
MPhil. Economics
Keywords: Ghana; Investment; Expenditure; Government; Private